Fundamentals of natural gas processing - Kidnay, Arthur J.; Parrish, William R.; McCartney, Daniel G. (Boca Raton, FL : CRC Press, 2011)
"Updated to cover new advances, this book introduces the natural gas industry to readers new to the field or those providing a narrow service who would benefit from an understanding of the overall process. The initial chapters give a brief overview of basic concepts applicable throughout the chemical processing industry. The second part addresses natural gas processing, following the gas stream from purchase at the wellhead to its entrance at the market place. Wherever possible, advantages, limitations, and ranges of applicability of various processes are discussed so that their integration into the overall gas plant can be fully appreciated"--Provided by publisher.
Includes index.
Includes bibliographical references.
PME
english
Keywords: Gas industry; Natural gas